(untitled) (Research, Society and Development, 2021)
Anatomical studies found in cone beam computed tomography (CBCT) an optimal resource for the three-dimensional (3D) assessment of the head and neck. When it comes to the maxillary sinuses, CBCT enables a life-size reliable volumetric analysis. This study aimed to assess the age and sex-related changes of the maxillary sinuses using volumetric CBCT analysis. The sample consisted of CBCT scans of 112 male (n = 57) and female (n = 55) individuals (224 maxillary sinuses) distributed in 5 age categories: 20 |— 30, 31 |— 40, 41 |— 50, 51 |— 60 and > 60 years. Image acquisition was accomplished with the i-CAT Next Generation device set with voxel size of 0.25 mm and field of view that included the maxillary sinuses (retrospective sample collection from an existing database). Image segmentation was performed in itk-SNAP (www.itksnap.org) software. The volume (mm3) of the segmented sinuses was quantified and compared pairwise based on side (left and right), sex (male and female) and age (five groups). Differences between left and right sides volume were not statistically significant (p > 0.05). The mean volume of maxillary sinuses in males was 22% higher than females (p = 0.0001). Volumetric differences were not statistically significant between age categories for males and females (p > 0.05). The discriminant power of sinuses’ volume may support customized and patient-specific treatment planning based on sex.